Aplikasi Pemetaan terkait Semi-Inner Produk pada Ruang Bernorma Real - Aulia Khifah Futhona; Supama (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2021)
In this article, we give the properties of mappings associated with the upper semi-inner product , lower semi-inner product and Lumer semi-inner product which generate the norm on a real normed space. Furthermore, we establish applications to the Birkhoff orthogonality and characterization of best approximants.